IMPACT OF PHARMACY TECHNICIAN-LED MEDICATION RECONCILIATION ON ADVERSE DRUG EVENTS AMONG HIGH-RISK PATIENTS ADMITTED TO SAUDI HOSPITALS: A CROSS SECTIONAL STUDY - Salman Mohammad Alshammari, Abdullah Faraj Alrashidi, Bandar malih aldhafeeri, Waleed Aodah Alenazi, Saad Saleh Alenazi, (Chelonian Research Foundation, 2022)
Medication reconciliation is a vital process to obtain an accurate list of patients’ current home medications upon hospital admission to avoid potentially harmful errors. While traditionally performed by pharmacists, training pharmacy technicians to conduct reconciliation may expand this key safety service. However, minimal evidence examines impacts of pharmacy technician-led reconciliation programs specifically within Saudi Arabian hospital settings. This cross-sectional study aimed to address this gap by comparing rates of adverse drug events between 257 high-risk patients receiving technician-led medication reconciliation versus standard physician reconciliation at two comparable hospitals over a 6 month period. Results demonstrated the hospital utilizing trained pharmacy technicians for reconciliation had significantly lower rates of overall adverse drug events (12% versus 22%, p<0.01) and serious adverse drug events (2% versus 8%, p<0.05) compared to the standard physician reconciliation hospital. Findings support the potential role of pharmacy technicians in improving medication safety through reconciliation services for vulnerable high-risk patients in Saudi hospitals. Further expansion and evaluation of technician-led reconciliation programs is warranted.